Interpretasi Hukum Mutatis Mutandis Dalam Pembentukan Peraturan Daerah - Latuny, Jhon Alberth; Salmon, Hendrik; Mustamu, Julista (Postgraduate Program in Law, Universitas Pattimura, 2024)
Introduction: In the formation of regional regulations, one must look at the needs and existence of the region by prioritizing community welfare as an instrument in implementing regional regulations. This results in the formation of regional regulations having to be based on regional needs, not on legal rules, bearing in mind that application mutatis mutandis is the basis in seeing that need.Purposes of the Research: This writing aims to determine the study of mutatis mutandis legal interpretation in the formation of regional regulations. Methods of the Research: Normative legal research. The research approach is a statutory approach and a conceptual approach. The sources of legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The technique for collecting legal materials is through literature study and then analyzed through perspective using qualitative methods.Results of the Research: With the interpretation methods used such as literal, historical, systematic, teleological interpretation, or comparison with other laws. So that the formation of regional regulations by applying the mutatis mutandis principle becomes the main point in the formation of regional regulations based on more specific community needs, bearing in mind that this is useful for speeding up and making efficient the process of forming regional regulations.